Effects of continuously infusing glucose or casein into the terminal ileum on biomarkers of metabolism, inflammation, and intestinal morphology in growing pigs. (20th May 2021) - Mayorga, Edith J; Horst, Erin A; Al-Qaisi, Mohmmad; Goetz, Brady M; Abeyta, Megan A; Rodríguez-Jiménez, Sonia; Lei, Samantha; Acosta, Jesus A; Patience, John F; Serao, Mariana C Rossoni; Baumgard, Lance H
Abstract: Study objectives were to determine the effects of continuously infusing glucose (GLC) or casein (CAS) into the terminal ileum on biomarkers of metabolism, inflammation, and intestinal morphology in growing pigs. Crossbred gilts ( n = 19; 81 ± 3 kg body weight [BW]) previously fitted with T-cannulas at terminal ileum were used in the current experiment. Following 4 d of acclimation, pigs were enrolled in 2 experimental 4-d periods (P). During P1, pigs were housed in individual pens and fed ad libitum for collection of baseline parameters. At the beginning of P2, pigs were assigned to 1 of 3 infusion treatments: 1) control (CON; water; 3 liters/d; n = 7), 2) GLC (dextrose 50%; 500 g/d; n = 6;), or 3) CAS (casein sodium salt; 300 g/d; n = 6). Water, GLC, and CAS solutions were continuously infused at a rate of 125 mL/h for the entirety of P2. Animals were euthanized at the end of P2, and intestinal tissue was collected. During P2, average daily feed intake differed across treatments and was reduced in GLC compared with CON pigs (14%), while CAS pigs consumed an intermediate amount ( P = 0.05). Average daily gain and final BW were similar across treatments. A treatment by time interaction was observed for blood urea nitrogen (BUN; P < 0.01), as it decreased in GLC (21%) while it gradually increased in CAS (76%) pigs relative to CON pigs. Mild hyperthermia occurred with both GLC and CAS infusions relative to CON (+0.3 and 0.2 °C, respectively; P < 0.01). Blood neutrophils increased in CAS relative to CON pigs (26%) but remained similar between CON and GLC treatments ( P < 0.01). Blood monocytes decreased in GLC relative to CON pigs (24%) while CAS pigs had an intermediate value ( P = 0.03). Circulating lipopolysaccharide binding protein tended to decrease in GLC (29%) relative to CON pigs but remained similar between CON and CAS pigs ( P = 0.10). Plasma tumor necrosis factor-alpha was similar across treatments. Ileum villus height:crypt depth was increased in CAS compared with CON pigs (33%; P = 0.05) while GLC pigs had an intermediate value. Colon myeloperoxidase-stained area increased in CAS compared with CON pigs (45%; P = 0.03) but remained similar between GLC and CON pigs. In summary, continuously infusing GLC or CAS into the terminal ileum appeared to stimulate a mild immune response and differently altered BUN patterns but had little or no effects on blood inflammatory markers, intestinal morphology, or key production parameters.